(untitled) (Journal of history-rus, 2023)
The article presents the results of scientific research carried out in the 2022 field season at the Saryoba archaeological complex, located in the Zhaksy district of Akmola region, near the confluence of the Yesil and Terisakkan rivers. The archaeological complex of Saryoba contains funerary, cult and ritual objects dating from ancient times to the late Qazaq time. The core of the complex is a large mound with a diameter of 100 m and a height of 3.85 m . Prior to the start of archaeological excavations, geophysical studies were carried out at this site. The results of the study recorded an anomaly in the structure of the embankment. During archaeological excavations on the mound, burials of medieval and late Qazaq times were discovered, a excavation was laid along the north-south and east-west lines. As a result, structures of the Kipchak period and burials of the late Qazaq period were found in the upper part of the embankment. Laboratory analyses of the found archaeological materials (anthropological, ceramological, radiocarbon, etc.) were carried out. Since the research in the archaeological complex of Saryoba is planned for several years, it is planned to continue the excavations in the following years. According to preliminary data, the Large Mound investigated in the archaeological complex of Saryoba is an elite burial and ritual object dating from the early Iron Age. Keywords: Saryarka, Yesil, Saryoba, archeology, burial ground, kurgan.